Buddhist Community Empowerment in Health - Kelvin, Kelvin; Surjano, Irvan; Kabri, Kabri (Institut Manajemen Wiyata Indonesia, 2024)
Empowering Buddhist communities in the health sector includes a series of concepts, views, and practices that integrate Buddhist religious values with health aspects. The concept of health empowerment, as the main foundation, provides a philosophical basis for efforts to improve the welfare of Buddhist communities. Furthermore, the Buddhist concept of health introduces a holistic view that includes physical, mental, and spiritual aspects as interrelated elements in achieving optimal health. The Buddhist approach to health emphasizes the principles of morality, awareness, and wisdom in maintaining a balanced life. Health science according to Buddhism provides an in-depth knowledge base regarding the relationship between mind and body, as well as ways to maintain overall health. Empowering herbal plants for health is one of the real implementations through exploring the potential of plants as a source of natural medicine. Mental health aspects from a Buddhist perspective are the main focus of community empowerment efforts. By adopting meditation practices and understanding the concept of dukkha (dissatisfaction), Buddhist communities can manage stress and improve their mental well-being. Apart from that, the development of health sciences also raises ethical controversies that need to be accommodated through a Buddhist perspective, integrating advances in science with the moral values believed in by the Buddhist community. Strengthening public health from a Buddhist perspective encourages active community participation in maintaining and improving collective health. By understanding and applying Buddhist teachings, people can form a proactive mindset towards health, build solidarity, and realize shared prosperity. Empowering the Buddhist community in the health sector is a vehicle for implementing religious values in improving the overall quality of life.